Implementasi Pembelajaran Kewirausahaan dalam Pembentukan Karakter Mandiri Siswa Kelas XI Madrasah Aliyah Entrepreneur Nurul Qolbi Polorejo Babadan Ponorogo - Oktavia Marfuatul Maslikhah; Ririn Nuraini (Tarbawi: Journal of Islamic Education, 2022)
This study aims to explain entrepreneurial learning, explain the inhibiting and supporting factors for the implementation of entrepreneurship learning in the formation of students' independent character and explain the implementation of entrepreneurship learning in the formation of independent character in class XI Madrasah Aliyah Entrepreneurial Lessons Nurul Qolbi. This study uses data collection techniques through interviews, observation and documentation. The data analysis technique uses an interactive model from Milles and Hubarman in the form of data reduction, data presentation and drawing conclusions. This study resulted in the following conclusions: Based on research on the implementation of entrepreneurship learning in the formation of independent character of class XI students of Madrasah Aliyah "Entrepreneur" Nurul Qolbi, it can be concluded as, Entrepreneurship learning at Madrasah Aliyah "Entrepreneur" Nurul Qolbi is one form of effort to study the potential student skills. Entrepreneurship learning is to begin to form an independent character attitude. the inhibiting factor is the lack of awareness in learning and motivation to learn, while the supporting factors emphasize practical learning and open government. Implementation of Entrepreneurship Learning at Madrasah Aliyah "Entrepreneur" Nurul Qolbi applies learning using 20% ​​theory and 80% practice methods. Students come into direct contact with adequate fields and laboratories and students can channel their potential or talents.